Knowledge, Power and Being: Literature and the Creation of an Archive of "Marginal" Sexualities in the Maghreb. Issue 4 (1st October 2016) - Ncube, Gibson
Summary: This article analyses the role of literature in creating knowledge and an archive of "marginal" sexuality in the Maghreb. Cultural and religious discourses have functioned in a manner that has not only marginalised non-normative sexuality but, more importantly, rendered them invisible. The bourgeoning body of literary works that have dared to break the silence on such sexuality has played a pivotal role in establishing a significant archive of the marginalised lives of lesbian, gay, bisexual and transgender (LGBT) individuals in Arab-Muslim Maghreb. Drawing on Jacques Derrida's postulations on the archive, this article contends that the construction of an archive of "marginal" sexuality involves a questioning and challenging of the existing hegemonic heteronormative archive of sexuality in the Maghreb. This heteronormative archive has of course deliberately omitted non-normative sexualities which have been rendered taboo and unsayable. This article will show that in the quest to remember these marginalised sexualities; the project to construct an archive and knowledge of "marginal" sexualities relies greatly on the French archive of nonnormative sexualities. This reliance is however imbued with agency considering how the selected corpus of literary texts also destabilise the orientalist gaze which has constructed Maghrebian sexualities as exotic and "other".